Analisis Perbandingan Nilai Signal to Noise Ratio (SNR) pada Pemeriksaan MRI Ankle Joint dengan Menggunakan Quad Knee Coil dan Flex/Multipurpose Coil - Ahda Nur Arifah; Yeti Kartikasari; Emi Murniati (Jurnal Imejing Diagnostik (JImeD), 2017)
Background : Research on the difference comparison the value of Signal To Noise Ratio (SNR) at MRI Ankle Joint examination using Quad Knee Coil and Flex/Multipurpose Coil at the hospital's radiology installation Telogorejo Semarang. Quad knee coil is a volume coil, is a coil that can act as a transmitter and receiver at the same RF signal (transreceiver). Flex / Multipurpose Coil is a surface coil which has a high SNR for a superficial examination (a small organ). The purpose of this research is to know comparison the value of signal to noise ratio (SNR) and higher the value of signal to noise ratio (SNR) at MRI Ankle Joint examination using Quad Knee Coil and Flex / Multipurpose Coil.Method : This type of research is quantitative experimental approach. The research data which 6 samples. Rate includes images subjectively talocalcaneal interosseous ligament, talocrural joint, subtalar joint, the calcaneus, tibia, talus, and the Achilles tendon. Then the results of the data in Paired T-Test tested.Results : Test results that there are differences in comparison the value of signal to noise ratio (SNR) at MRI Ankle Joint examination using Quad Knee Coil and Flex / Multipurpose Coil which has a p-value / sig for all of 0.002, and each criterion that have talocalcaneal interoseous ligament p value 0.026, talocrural joint p value 0.017, subtalar joint p value 0.001, calcaneus p value 0.002, tibia p value 0.003, talus p value 0.006, and achilles tendon p value 0.012. This is in accordance with the calculated average value SNR on the use of Quad Knee Coil is higher at 110.67 because the coil acts as transreceiver and has two preamplifier so as to improve the SNRConclusion : There is a differences in comparison the value of Signal To Noise Ratio (SNR) at MRI Ankle Joint examination using Quad Knee Coil and Flex / Multipurpose Coil.